The use and abuse of graphs in annual reports - Ang, Wan Choon (2013)
This study investigate the use and abuse of graphs in a Singapore context. We found that improperly constructed graphs can significantly influence people’s perception of corporate performance. From an analysis of the annual reports of 100 companies listed on Singapore Stock Exchange for the year ended 1994 or 1995, we have documented the nature and extent of graph usage. The average number of graphs per annual report is 3.3, with turnover, profit and assets as the three most commonly graphed variables. Our analysis also provides statistical evidence of selectivity in the use of graphs. Companies with ‘good performance’ are significantly more likely to use graphs. Non-compliance with the principles of graph construction that results in material measurement distortion occurs in 54% of these graphs, with the underlying data being exaggerated by an average of21.9%. It was found statistically that these measurement distortions are likely to give a more rather than a less favorable portrayal of the company’s performance. We conclude that auditors’ and directors’ responsibilities in this area should be made more explicit. We also express concern over the lack of authoritative guidance to assist auditors in determining whether a graph is materially inconsistent with the accompanying financial statements.